Does China’s competitive generic substitution policy deliver equivalent clinical outcomes? A pilot study with two generic formulations of olanzepine - Zhang, Chao; Ding, Yudan; Wu, Zhenzhen; Wang, Juan; Wu, Xiangping; Xie, Weiwei (Frontiers in Pharmacology, 2023)
With the National Centralized Drug Procurement policy gradually applied nationally in China, concerns about the effectiveness and safety of bid-winning generic drugs and the clinical effects of generic-generic switch are growing again. This real-world study was conducted to fill the gap. Results suggest that a generic version of a psychotropic medication may not be of therapeutic equivalence or bioequivalence with another generic one. Changes in efficacy or tolerability are possible in every switch. Therapeutic drug monitoring could be a valuable tool during switches between generic drugs. Larger prospective clinical studies for other generic psychotropic medications in target populations are warranted.